2018
DOI: 10.1159/000487011
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Surgery: Robotic Surgery versus Laparoscopic Procedures for Esophageal Malignancy

Abstract: Background: The evolution of minimally invasive surgery (MIS) also extends to the field of esophageal surgery and has brought forth the development of several approaches of minimally invasive esophagectomy (MIE). Hybrid and total minimally invasive operative techniques have proven beneficial compared to open surgery and are currently evaluated against robotic-assisted minimally invasive esophagectomy (RAMIE). We aim to review the current literature regarding the position of MIE versus RAMIE. Methods: A systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…33,34 Other studies have shown that robotic assisted esophagectomy is technically feasible and has proven good short-term oncologic outcomes. 35 Abbott et al report a cohort of 134 patients finding that the complication rate in patients over the age of 70 years is comparable to younger patients. 36 They also report favorable outcomes for patient with larger body mass index, with comparable operative times and postoperative complication rates.…”
Section: Discussionmentioning
confidence: 98%
“…33,34 Other studies have shown that robotic assisted esophagectomy is technically feasible and has proven good short-term oncologic outcomes. 35 Abbott et al report a cohort of 134 patients finding that the complication rate in patients over the age of 70 years is comparable to younger patients. 36 They also report favorable outcomes for patient with larger body mass index, with comparable operative times and postoperative complication rates.…”
Section: Discussionmentioning
confidence: 98%
“…Transhiatal RAMIE was first introduced in 2003 [11] , and transthoracic RAMIE was introduced a year later [12] . Although RAMIE is still under development, it is now described as a promising minimally invasive operative method with short-term and long-term clinical outcomes that are equivalent to (or perhaps better than) those achieved with OE and MIE [ Table 2] [29] . In a US report, 32.1% of esophageal cancer patients were treated with MIE.…”
Section: Characteristics Of the Operative Approaches To Esophagectomymentioning
confidence: 99%
“…8). However, it will be difficult to prove a better clinical outcome for the patient compared to conventional MIE [75].…”
Section: Roboticmentioning
confidence: 99%